Paul's idea of community the early house churches in their cultural setting - Banks, Robert John, 1939- (Peabody, MA Hendrickson, 1994)
Includes bibliographical references.
Original edition published 1979 by ANZEA, Homebush West, NSW, which see also.
Keywords: House churches -- church history -- primitive and early church, ca. 30-600 -- Rome; Bible. N.T. Epistles of Paul -- theology; Church -- biblical teaching; Freedom (theology) -- biblical teaching